Relations among self-control, hope, and psychological adjustment: A two-wave longitudinal mediation study - Deniz, M. Engin; Satici, Seydi Ahmet; Okur, Sinan; Satici, Begum (WILEY, 2023)
While the relationships between self-control, hope, and psychological adjustment have been examined in cross-sectional studies, the fact that these variables have not been considered together in any longitudinal research creates a gap in the literature. Therefore, our study aimed to investigate the longitudinal relationships between self-control, hope, and psychological adjustment. Specifically, a cross-lagged panel study in two waves was conducted to examine whether hope mediated the association between self-control and psychological adjustment using a Turkish college sample (N = 349). The results revealed that hope had a significant mediation effect in the longitudinal association between self-control and psychological adjustment. In this direction, self-control indirectly predicts psychological adjustment through hope. This longitudinal study reveals that having self-control may have a positive influence on a person's level of hope and that hope may be a significant predictor of individual psychological adjustment.
Keywords: Self-control; hope; psychological adjustment; longitudinal mediation; INDIVIDUAL-DIFFERENCES; RACIAL-DISCRIMINATION; SOCIAL SUPPORT; ADULTS; Psychology